2022
DOI: 10.1177/21582440221094820
|View full text |Cite
|
Sign up to set email alerts
|

Academic Hatred: Focusing on the Influence of a Supportive Classroom Climate

Abstract: This study aimed to examine the effects of interpersonal factors (i.e., teacher and peers) on academic hatred using the hierarchical linear model analysis. The data were collected from 1,015 senior high school students from 43 classrooms (57.3% female) in South Korea. The results showed significant effects of teachers’ academic pressure, autonomy support, and peer support on academic hatred at both the individual and classroom levels. Interestingly, teachers’ academic pressure showed different effects on acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…As Skinner et al (2008) postulated in their model, students who perceived teachers' support positively were more likely to feel satisfied psychologically and then engage more in their learning, ultimately achieving higher attainment of learning. Previous studies on EFL learning also support these assumptions (e.g., Dincer et al, 2019;Lee et al, 2022). Dincer et al (2019) showed that academic English learners who received positive teacher autonomy support were more likely to demonstrate a higher sense of satisfaction and active involvement in the language classroom, thereby increasing the likelihood of obtaining higher grades.…”
Section: Classroom Engagement In Language Learningmentioning
confidence: 77%
See 2 more Smart Citations
“…As Skinner et al (2008) postulated in their model, students who perceived teachers' support positively were more likely to feel satisfied psychologically and then engage more in their learning, ultimately achieving higher attainment of learning. Previous studies on EFL learning also support these assumptions (e.g., Dincer et al, 2019;Lee et al, 2022). Dincer et al (2019) showed that academic English learners who received positive teacher autonomy support were more likely to demonstrate a higher sense of satisfaction and active involvement in the language classroom, thereby increasing the likelihood of obtaining higher grades.…”
Section: Classroom Engagement In Language Learningmentioning
confidence: 77%
“…Based on a large-scale investigation of English speaking learning among Chinese university students, Peng and Woodrow (2010) established that teacher support indirectly predicted students’ engagement in speaking tasks by mediating self-determined perception of their competence (one of the basic psychological needs). Lee et al (2022) also suggested that students with greater autonomy in choosing their favorite speaking tasks would experience greater psychological satisfaction and thus improve their learning engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatred academics is a dimension of academic burnout. Lee et al, (2022) show that apart from being related to changes in individual student characteristics, academic pressure also has an impact on academic results. Students with high academic pressure will avoid academic matters.…”
Section: Hatred Academicmentioning
confidence: 97%